PENGARUH LATIHAN RESISTENSI TERHADAP KADAR HBA1C LANSIA DENGAN DIABETES MELITUS TIPE 2: A SYSTEMATIC REVIEW - Fitriani, Fitriani; Rekawati, Etty; Sahar, Junaiti; Rachmawati, Utami (Poltekkes Kemenkes Bandung, 2024)
Type 2 diabetes mellitus is a common metabolic disorder that often occurs in the elderly. One key component in diabetes management is physical activity. Various studies have been conducted to examine the effectiveness of physical exercise on glycemic control and it has been found that physical exercise can improve insulin sensitivity and glycemic control. The research aimed to identify the impact of resistance exercise on HbA1c in elderly individuals with diabetes. Research method with systematic review on ProQuest, Scopus, PubMed, EBSCO Host, Clinical Key Nursing, and Science Direct databases. The inclusion criteria were articles published between 2018 and 2023 in the English language. A total of 7,812 articles were found based on the keywords (Older adult OR elderly OR aged OR Older People OR Older person) AND (type 2 diabetes OR diabetes OR diabetes mellitus OR Noninsulin Dependent Diabetes Mellitus OR NIDDM OR Diabetes Mellitus Type II) AND (